Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The textbook I'm reading derives it like this:

$\eqalign{ & y = \sin x \Rightarrow \left( 1 \right) \cr & y + \delta y = \sin (x + \delta x) \Rightarrow (2) \cr} $

Subtracting equation (1) from (2):

$\eqalign{ & y + \delta y - y = \sin (x + \delta x) - \sin x \cr & \delta y = \sin (x + \delta x) - \sin x \cr & = 2\cos (x + {1 \over 2}\delta x)\sin \left({1 \over 2}\delta x\right) \cr} $

Without completing the whole "proof" I can tell you where I am confused.

$\delta y = \sin (x + \delta x) - \sin x$

to this:

$2\cos (x + {1 \over 2}\delta x)\sin \left({1 \over 2}\delta x\right)$

What happened here? It looks like the double angle identity was used? Isn't the double angle formula used for when two angles are the same? I know dx is very small, but still, the value of x has been altered so shouldn't the "angle addition" identity be used instead? Further more what happened to the -sin(x)? How was it incorporated into $2\cos (x + {1 \over 2}\delta x)\sin \left({1 \over 2}\delta x\right)$ ?

This is confusing me quite a bit, any help would be greatly appreciated, thank you.

EDIT: Furthermore, 1/2(dx): where does this come from?

share|cite|improve this question
You need the formula for sinus of the sum of two angles, not the twice angle formula! You certainly find that in wikipedia. – kjetil b halvorsen Apr 16 '13 at 11:02
up vote 3 down vote accepted

To prove that formula just use

Let $\alpha = A+B, \beta = A-B$. Then note that $\alpha +\beta =2A$ and $\alpha - \beta=2B$. Now you have $A=\displaystyle \frac{\alpha+\beta}{2}$ and $B=\displaystyle \frac{\alpha-\beta}{2}$

\begin{align*} \sin(\alpha)-\sin(\beta) &= \sin(A+B) - \sin(A-B) \\ &= \sin(A)\cdot\cos(B) + \cos(A)\cdot \sin(B) - \sin(A)\cdot\cos(B)+\cos(A)\cdot\sin(B) \\ &=2 \cdot \cos(A) \cdot \sin(B) \\ &= 2 \cdot \cos\left(\frac{\alpha+\beta}{2}\right) \cdot \sin\left(\frac{\alpha-\beta}{2}\right) \end{align*}

$\Large\text{Method 2}$

\begin{align*} f'(x) &= \lim_{\delta x\to 0} \frac{\sin(x+\delta{x}) -\sin(x)}{\delta{x}} \\ &=\lim_{\delta{x}\to0} \frac{\sin(x)\cdot\cos(\delta{x}) +\cos(x)\cdot\sin\delta{x} -\sin(x)}{\delta{x}} \\ &=\lim_{\delta{x}\to0} \frac{\sin(x)\cdot \bigl(\cos(\delta{x})-1\bigr)}{\delta{x}} + \lim_{\delta{x}\to 0}\frac{\cos{x}\cdot \sin(\delta{x})}{\delta{x}} \\ &= \lim_{\delta{x}\to 0} \frac{\sin(x)\cdot \bigl(\cos(\delta{x})-1\bigr)}{\delta{x}} + \cos(x) \qquad \Bigl[\because \small{\lim_{x\to 0} \frac{\sin{x}}{x}=1} \Bigr] \end{align*}

Now i leave it to you to prove $\displaystyle\lim_{\delta{x}\to 0}\frac{\sin(x)\cdot \bigl(\cos(\delta{x})-1\bigr)}{\delta{x}} =0$. This can be proved by observing that $1-\cos(2x) = 2\cdot \sin^{2}(x)$.

share|cite|improve this answer

There was used a well-known formula $$\sin{\alpha}-\sin{\beta}=2\cos{\dfrac{\alpha+\beta}{2}}\sin{\dfrac{\alpha-\beta}{2}}.$$

share|cite|improve this answer
I didn't know it... – Ben Millwood Apr 16 '13 at 11:01
I see, thank you! – seeker Apr 16 '13 at 11:02

Recall the identities $\sin(A+B)=\sin A\cos B+\cos A\sin B$ and its close relative $\sin(A-B)=\sin A\cos B-\cos A\sin B$. Subtract. We get $$\sin(A+B)-\sin(A-B)=2\cos A\sin B.$$ Let $A+B=s$ and $A-B=t$. Then $A=\frac{s+t}{2}$ and $B=\frac{s-t}{2}$. So we obtain $$\sin s-\sin t=2\cos\left(\frac{s+t}{2} \right) \sin\left(\frac{s-t}{2} \right).$$

Remark: We give a somewhat different derivation of the derivative formula, that I think is a little easier for students. We also change notation slightly for ease of typing.

We are interested in the behaviour of $\frac{\sin(x+h)-\sin x}{h}$ as $h$ approaches $0$. The top is $\sin x\cos h=\cos x \sin h$. Divide by $h$ and rearrange slightly. We get $$\cos x\frac{\sin h}{h} -\sin x\frac{1-\cos h}{h}.$$ Let $h\to 0$. What happens to the first part is familiar. As for $\frac{1-\cos h}{h}$, multiply top and bottom by $1+\cos h$. We get $$\frac{1}{1+\cos h}\frac{\sin^2 h}{h}.$$ Since $\frac{\sin h}{h}$ has limit $1$, we conclude that $\frac{\sin^2 h}{h}$ has limit $0$.

share|cite|improve this answer
Yep, got it, thanks. – seeker Apr 16 '13 at 11:18

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.